Clinical profile and outcome of infant of diabetic mother in a tertiary care sick newborn care units - Senthilkumar, K. M.; Shanthi, R. (International Journal of Contemporary Pediatrics, 2020)
Background: Diabetes mellitus is the most common metabolic disorder complicating pregnancy. The incidence of pre-gestational (type 1 and type 2) and gestational diabetes mellitus is on the rise in India. Authors aimed to study the clinical profile and outcome of the infant of diabetic mothers. Methods: The study was conducted in the Sick Newborn Care Unit attached to Stanley Medical College in Chennai over a period of 6 months. All infants born to diabetic mothers during the study period were included in the study. Results: Among the total of 6236 babies delivered in total during the study period, 566 (9.07%) were born to diabetic mothers. 16.25% were pre-gestational diabetic mothers and 83.75% were GDM Mothers. The incidence of prematurity was 15.2% and LGA was 7.9%. The majority were AGA (495 out of 566). Symptomatic Hypoglycemia was observed in 16 babies and asymptomatic hypoglycemia in 35 babies with total occurrence of hypoglycemia in 9% of babies. Hyper-bilirubinemia is the most common problem encountered in 29% of babies, congenital heart disease and renal problems were the most common congenital anomalies noted in IDM 44 out of 566 babies (7.8%). Conclusions: There is lack of awareness regarding dog bite and its management among the rural populatEarly detection and optimal management of diabetic status during the antenatal period along with anticipation, early recognition and management of postnatal complications will reduce the mortality of infants of diabetic mothersion.